Printmaking : a contemporary perspective - Coldwell, Paul (London, UK : Black Dog Pub., 2010)
Review of the art of printmaking, focusing on the contemporary approaches to the medium. Includes work from all over the world, profiling some of the most innovative examples of printmaking today. Artists featured include Grayson Perry, Thomas Kilpper, Patrick Caulfield, Marko Blazo, Chuck Close, Masami Teraoka, Michael Craig-Martin, Kara Walker, Willie Cole, Banksy, and others
-- Reworking traditions -- Painterly approaches -- The hybrid print -- Political imperatives -- The sculptor's print -- Expanded print -- New technology new opportunities
Includes bibliographical references (pages 188-189)
Keywords: Prints -- Technique; Printmakers; Prints -- History